Flow accelerated corrosion rate on carbon steel pipe bend by thin layer activation technique and computational modeling: Under PHWR operating conditions. (March 2021) - Madasamy, P.; Chandramohan, P.; Mukunthan, M.; Krishna Mohan, T.V.; Rangarajan, S.; Uttam, Niraj; Ramakrishnan, R.; Babulal, G.; Rani, H.P.; Surendran, P.; Gupta, A.K.; Nair, J.P.
Highlights: Carbon Steel pipe corrosion in 50NB Sch 160 of bend angle 58° radius 4 times diameter. Specimen welded to HTHP loop irradiated with proton beam for nuclear reaction. In loop pH (10.2) DO (<5 ppb) at 290 °C/87 bar maintained by adding LiOH and N2 H4 . Corrosion rate measured by TLA method. CFD simulated corrosion rate coincides with that of TLA method. Abstract: Carbon Steel (CS) piping plays a vital role in the heat transport circuits of power plants. These pipes undergo excessive degradation in some of the specific locations due to the flow dynamics variation and such corrosion is termed as the flow accelerated corrosion (FAC). The corrosion rate is usually estimated at a specific location based on one of the best available technique known as the Think Layer Activation (TLA) method. In the present study this method was adopted for the estimation of CS pipe corrosion with 50NB Sch 160, bend angle of 58° and 4D bend radius (D-pipe diameter). Irradiated location was chosen based on the turbulence patterns in the bend as mapped by CFD analysis. At the specified location the corrosion rate to be monitored was irradiated with the proton beam of 13.3 MeV energy aiming for the nuclear reaction of Fe 56 (p, n) Co 56 . This irradiated specimen was welded to the High Temperature High Pressure (HTHP) loop and operated at 290 °C/87 bar. The chemistry parameters like pH (10.2) and DO (< 5 ppb) in the loop were maintained by suitably adding LiOH and N2 H4 . Corrosion rate was assessed by measuring the radioactivity decrease due to corrosion. Throughout the experimental duration the radioactivity measurement was carried on the CS pipe surface at the fixed distance locations. The flow structure in the considered geometry is simulated using CFD. The flow field, velocity, is used to calculate the wall shear stress and mass transfer coefficient. The corrosion rate is calculated with the help of Chilton-Calbourn Equation. It is observed that the computed corrosion rate for this CS pipe under this chemistry and geometry conditions was 400um/y which coincides with that of the TLA method.